The evolution of urban music in Democratic Republic of the Congo during the 2nd and 3rd decades (1975-1995) of the Second Republic-Zaire - wa Mukuna, Kazadi (International Library of African Music, 1999)
Elsewhere, I argue that the implementation of the quota system in higher education in the 1960s was one of the catalysts for the rise of a large new generation of musicians and musical ensembles in Zaire during the first decade of the Second Republic. In the same source I assert that the musical style of the younger generation of musicians was laden with borrowings of phrasing referents (time-line patterns) and melodic formulae from ethnic music. Unlike the first, the last two decades of the Second Republic, stigmatized by the sagging economy and die decadence of the political structure, sent a series of negative impacts to all facets of the national life, culminating in the closing of the chapter on President Mobutu's thirty-two year regime (May 20, 1965 through May 17, 1997). The failed attempt by the government to eradicate tribalism reinforced instead ethnic consciousness, whose lasting effect continues to be felt well after the May 17 liberation. While becoming indifferent to the political regime and its leadership, musicians remained faithful to their respective ethnic traditions, and reflected this ethnic awareness in the newly established style. These two realities prevailed during the last two decades of the Second Republic as sources of inspiration as the situation compounded.
Keywords: Music; African Music; Democratic Republic of the Congo; Urban Music; Zaire